Mulheres no poder: a dimensão machista na trama do golpe contra Dilma Rousseff - Vieira, Liliane Cirino (2022)
This research aims to discuss the sexist dimension of the coup against Dilma Rousseff, its impact on feminism and the process of “(dis)empowerment” of women in Brazilian politics, when considering what these female representations in parliament officially mean, given the premise of the sexist symbology that caused the overthrow, in 2016, of the first female president of Brazil. While the introduction addresses the historical and political context in which this research was conceived and concisely discusses the theoretical basis and sections of the work, the first section provides a brief recap on the participation of women in Brazilian politics after the Proclamation of the Republic in 1889, as well as the discussion about women’s struggle for democracy and respect in the political sphere. In turn, the second section concerns the sexist dimension, by pointing out the fields of dispute for women; discuss how part of the national press contributed to the ideological propagation of machismo and misogyny by manipulating reports. Therefore, it is intended to verify how misogyny and sexism were used, especially by the press, as a political weapon against Dilma Rousseff, in addition to debating how the policies of inclusion of women and diversity annoyed the ultraconservative sectors, i.e., how the conquest of rights aroused the anger of this reactionary camp, which culminated in the propagation of slander and misogynistic insults against the president. The third section brings a brief chronology of Partido dos Trabalhadores (PT, in Portuguese abbreviation) government from a certain perspective, by associating the 2016 coup to the rise of violent ultraconservative and reactionary groups, holders of misogynistic values, racist, LGBTphobic and who came to power after that event, in which the sources of the Annals of the Chamber of Deputies of April 17th, 2016 are used to analyze the justifications of deputies during the impeachment vote, investigate whether they represented sexist groups in society and indicate the field of disputes between the defenders of patriarchy and women’s resistance movements. The final considerations do not aspire to any definitive closure, since history is constantly being formulated, but rather outline the assumptions in a synthesized way and understand how such interpretations were reached. It is important to understand that this work does not aim to defend the hypothesis that the coup against Dilma Rousseff solely occurred as a result of (and consequence) of machismo – since there were other nuances such as the economic dimension that involve various interests, e.g. the purpose of privatizations, the reduction of rights in the working class, Pre-Salt, “Lava-Jato” Operation etc. –, but rather to explore the sexist dimension and the particularity of ideological propagation of machismo and sexism by the supporters of 2016 coup.